I need to prove using induction Asymptotic upper bound in Big-O for


So I tried expanding

$$\begin{align} T(n) &= T(n-1) + 3n - 5 \\ &= T(n-2)+ 2(3n-5) \\ &= T(1) + (n-1)(3n-5) \\ &= 3n^2-8n+6 \end{align}$$

Then I tried proving:

For $n=1$, $T(1)=3-8+6=1$
Assume solution correct for $n \le k-1$, we want to show its correct for $n=k$.

$$\begin{align} T(k) &= T(k-1)+3k-5 \\ &= 3(k-1)^2-8(k-1)+6+3k-5 \\ &= 3(k^2-2k+1)-8k+8+6+3k-5 \\ &= 3k^2-11k+12 \end{align}$$

Seems wrong?


There's a mistake at $T(n-2)+2(3n-5)$; that has to be $T(n-2)+(3n-5)+(3(n-1)-5)$. Do you want to see a better way to solve the recurrence? Or would you rather work on it a little longer?

EDIT: OP has asked for a better way, so here goes:

We have $$T(k)=T(k-1)+3k-5$$ for all $k$. Summing for $k$ from $1$ to $n$, that's $$\sum_{k=1}^nT(k)=\sum_{k=1}^nT(k-1)+\sum_{k=1}^n(3k-5)$$ Now $T(1),T(2),\dots,T(n-1)$ appear on both sides of the equation, so we cancel them, leaving $$T(n)=T(0)+\sum_{k=1}^n(3k-5)$$ So the question now is, do you know how to evaluate $\sum_{k=1}^n(3k-5)$?

  • $\begingroup$ I seem to intuitively think of expanding, and if I see any pattern, I could generalize. But I think you are suggesting theres a better way? I am always open to learning it :) ... expanding seems tedious tho ... $\endgroup$ – Jiew Meng Feb 5 '13 at 13:21
  • $\begingroup$ @JiewMeng Expanding a little bit helps: $$3\sum_{k=1}^n k-\sum_{k=1}^n 5$$ $\endgroup$ – Robert Mastragostino Feb 5 '13 at 23:03

If really the question is the one you described in your question, you might try to prove recursively that, for every $n\geqslant1$, $$ T(n)\leqslant2n^2+T(1). $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.